PENGARUH PEMBERIAN REWARD DAN PUNISHMENT TERHADAP SEMANGAT KERJA PADA KARYAWAN BUMN DI KOTA ENDE - Dua Mea, Maria Helena Carolinda (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2022)
This study aims to determine the effect of giving rewards and punishments on morale for BUMN employees in the city of Ende. The type of research used is quantitative research. The data analysis technique used is multiple linear regression analysis. Because the population cannot be ascertained, 98 respondents were determined as samples. From the results of statistical testing t for the variable of reward and punishment has a value of tcount > t table with a significance value of <0.05. This shows that the variable of reward and punishment has a significant effect on work morale. For the adjusted R square value of 0.444, this shows that the percentage of the effect of giving rewards and punishments on work morale is 44.4%. While the rest is influenced by other factors that are not explained in this study.